Larval experience and latent effects—metamorphosis is not a new beginning. - Pechenik, Jan A. (Tufts University. Tisch Library., 2017)
For many years ecologists have documented the remarkable within-species variation inherent in natural systems—for example, variability in juvenile growth rates, mortality rates, fecundities, time to reproductive maturity, the outcomes of competitive interactions, and tolerance to pollutants. Over the past 20 years, it has become increasingly apparent that at least some of this variation may reflect differences in embryonic or larval experiences. Such experiences may include delayed metamorphosis, short term starvation, short term salinity stress, or exposure to sublethal concentrations of pollutants or sublethal levels of ultra violet irradiation. Latent effects—effects that have their origins in early development but that are first exhibited in juveniles or adults—have now been documented among gastropods, bivalves, echinoderms, polychaetes, crustaceans, bryozoans, urochordates, and vertebrates. The extent to which latent effects alter ecological outcomes in natural populations in the field, and the mechanisms through which they are mediated are largely unexplored.